Hospedabilidade de cultivares de lúpulo (Humulus lupulus L.) e uso das folhas no controle de Meloidogyne javanica - Santos, Fábio Mulinari dos (2024)
Plant parasitic nematodes are responsible for significant productivity losses in the main agricultural crops in Brazil and around the world. Nematodes of the genus Meloidogyne are among the main causes of this damage. Traditionally, one of the most adopted approaches to control this plant parasitic nematode is the use of chemical nematicides. However, most available nematicides have many adverse effects on the environment. Thus, the search for less harmful and more accessible compounds has driven studies of new alternatives. In this context, research involving the use of antagonistic plants and their metabolites has been conducted with the aim of identifying species with potential for controlling phytonematodes. The use of residues from certain plant groups for the biofumigation technique represents an efficient and sustainable alternative. The objective of this study was to evaluate the response of the hop plant to infection by Meloidogyne javanica and the effectiveness of aqueous extracts and volatile organic compounds (VOCs) from the leaves of different hop cultivars in controlling the nematode, as well as the analysis of the volatilome of the material used. Hostability experiments revealed that the hop cultivars analyzed (Saaz, Comet, Zeus and Centennial) are susceptible to Meloidogyne javanica. In vitro tests were conducted with the extracts and VOCs on second instar juveniles (J2s) and eggs, revealing a significant nematicidal and ovicidal impact. Subsequently, when exposing these J2s to materials derived from hop leaves and then inoculating them on tomato roots, a reduction in the number of galls formed and eggs extracted from the roots was observed in treatments with aqueous extracts and VOCs. of the four cultivars tested. When using macerates of the four cultivars in biofumigation experiments, it was possible to observe in all cases a control effect from 1% of plant material incorporated into the substrate. The volatilome identified in hop leaves revealed the presence of 40 compounds in the Saaz cultivar, 42 compounds in the Centennial cultivar, 45 compounds in the Zeus cultivar and 49 compounds in the Comet cultivar. Among these compounds, several are known for their effectiveness in controlling microorganisms, such as: 1-Hexanol, 2-Hexenol (E), 1-Octenol, 3-Hexenol (E), 2-Hexenal (E), β-Ionone, 3-Hexenyl Acetate (Z), α-Humulene and β-Caryophyllene. In this context, hop leaves stood out as an important source for the discovery of new nematotoxic molecules, in addition to being valuable as a raw material in biofumigation techniques and for the formulation of pesticides based on plant products.